Penetration of Ultraviolet‐B Radiation in Oligotrophic Regions of the Oceans During the Malaspina 2010 Expedition. Issue 5 (24th May 2022) - Overmans, S.; Duarte, C. M.; Sobrino, C.; Iuculano, F.; Álvarez‐Salgado, X. A.; Agustí, S.
Abstract: Few studies have investigated ultraviolet (UV) radiation in the open ocean besides its harmful effects on organisms and influence on biogeochemical processes. Here, we assessed UV attenuation, with particular focus on UV‐B, across the (sub)tropical ocean during the Malaspina 2010 Circumnavigation. Vertical UV radiometer profiles together with Chl‐ a concentration, and UV absorption by CDOM ( a CDOM ( λ )) and by suspended particulate matter ( a p ( λ )) were measured at 117 stations. At photosynthetically active radiation (PAR) and across UV‐A and UV‐B wavelengths, the lowest downwelling attenuation coefficients ( K d ) during the expedition were recorded in ultra‐oligotrophic regions at 5°–15°S (mean K d (305 nm): 0.129 m −1, mean K d (313 nm): 0.107 m −1 ) in the Indian and South Pacific Oceans. The waters here were comparatively more transparent than at 5°–15°N (mean K d (305 nm): 0.239 m −1, mean K d (313 nm): 0.181 m −1 ) where equatorial upwelling occurs. K d was highest near the Costa Rica Dome ( K d (313 nm): 0.226 m −1 ) and at the confluence of the Benguela and Agulhas currents ( K d (313 nm): 0.251 m −1 ). The contribution of a p ( λ ) toward nonwater absorption ( a nw ( λ )) was significantly lower at 305 nm than at 313 and 320 nm, suggesting the contribution of absorption by detritus and phytoplankton particles decreases compared with that of CDOM absorption as UV‐B wavelength decreases. Both a CDOM ( λ ) and a p ( λ ) at UV‐B wavelengths were lowest in the Indian Ocean whereas K d was lowest in the South Pacific. This finding emphasizes that other factors besides absorption, such as scattering by reflective phytoplankton or inorganic particles, strongly influence UV‐B attenuation in open ocean waters. Plain Language Summary: We assessed water transparency to UV‐B radiation across the tropical and subtropical ocean as part of the Malaspina 2010 Expedition. UV‐B radiometer profiles, Chlorophyll‐ a, and UV‐B absorption by organic matter and suspended particles were measured at 117 stations. The most UV‐B transparent waters were found in regions where nutrients are extremely low, particularly at 5°–15°S in the Indian and South Pacific Oceans. Here, ocean waters were considerably more transparent than 5°–15°N, which suggests that at a given depth southern hemisphere marine organisms experience higher UV‐B exposure than their northern counterparts. The least UV‐B transparent waters were near the Costa Rica Dome and at the confluence of the Benguela and Agulhas currents. UV‐B absorption by organic matter and suspended particles, and Chl‐ a concentration were lowest in the Indian Ocean. The contribution of suspended particles toward nonwater absorption was significantly lower at 305 nm than at 313 and 320 nm, and higher in the clearest waters of the Indian Ocean than in the Subtropical South Pacific. Absorptions by organic matter and suspended particles were lowest in the Indian Ocean whereas UV‐B attenuation was lowest in the South Pacific, which highlights the complex relationship between optical properties in the UV‐B spectrum. Key Points: During the expedition, we found the 5°–15°S region contained the most UV‐B transparent waters Transparency to PAR was on average highest at ∼20° latitude in both hemispheres K d (UV‐B) was most strongly correlated with Chl‐ a, followed by a CDOM ( λ )